2018
DOI: 10.3989/scimar.04730.09a
|View full text |Cite
|
Sign up to set email alerts
|

Use of video monitoring to quantify spatial and temporal patterns in fishing activity across sectors at moored fish aggregating devices off Puerto Rico

Abstract: Summary:A key challenge in small-scale fisheries that use moored fish aggregating devices (mFADs) is the ability to accurately quantify multi-sector fishing activity through fishery-independent methods. Here, we present a novel fishery-independent assessment of multi-sector fishing activity associated with a newly developed open access mFAD programme off San Juan, Puerto Rico. We identified three fishing sectors (recreational, charter and commercial) and 158 individual fishing vessels that routinely operated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Multiple authors have advocated that autonomous camera systems could be cost‐effective means of estimating fishing effort, but few have demonstrated it through detailed analysis and direct comparison between a camera system and another technique. Our direct comparison of boat ramp cameras with concurrent roving creel surveys showed that substantially less time and money were required to operate boat ramp cameras than to conduct roving creel surveys, and these results are consistent with those of other studies that compared the costs of camera‐based fishing effort estimation and those of other techniques (Smallwood et al 2012; Merten et al 2018; Stahr and Knudsen 2018). In our comparison, roving creel surveys were 1.25–2.5 times as expensive as cameras.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Multiple authors have advocated that autonomous camera systems could be cost‐effective means of estimating fishing effort, but few have demonstrated it through detailed analysis and direct comparison between a camera system and another technique. Our direct comparison of boat ramp cameras with concurrent roving creel surveys showed that substantially less time and money were required to operate boat ramp cameras than to conduct roving creel surveys, and these results are consistent with those of other studies that compared the costs of camera‐based fishing effort estimation and those of other techniques (Smallwood et al 2012; Merten et al 2018; Stahr and Knudsen 2018). In our comparison, roving creel surveys were 1.25–2.5 times as expensive as cameras.…”
Section: Discussionsupporting
confidence: 88%
“…Gibson ESTIMATING FISHING EFFORT USING BOAT RAMP CAMERAS boat ramp cameras than to conduct roving creel surveys, and these results are consistent with those of other studies that compared the costs of camera-based fishing effort estimation and those of other techniques (Smallwood et al 2012;Merten et al 2018;Stahr and Knudsen 2018). In our comparison, roving creel surveys were 1.25-2.5 times as expensive as cameras.…”
Section: Apopkasupporting
confidence: 90%
See 1 more Smart Citation
“…In the new era of science, cameras are used frequently (Struthers et al, 2015), especially when scuba diving (e.g. Cook et al, 2013) and along with fisheries gear (Cairns et al, 2017;Merten et al, 2018). Moreover, the use of underwater photography and videography has proven to be useful at detecting alien species (e.g.…”
Section: Crustacean Research 48mentioning
confidence: 99%
“…Casa de Campo and Punta Cana), where they commonly overlapped with established artisanal FAD sites (Bareuther, 2016; Wilson et al, 2020). In addition, within the last several years, Puerto Rico and the USVIs have initiated new open‐access mFAD programs, following the Hawaiian model (Holland & Jaffe, 2000), which led to a re‐emergence of recreational FAD use and increased multi‐sector overlap at these sites (Merten et al, 2018). The emergence of mFADs in waters around Puerto Rico and the USVIs introduced a priority to investigate dolphinfish behaviour and fishery dynamics (e.g.…”
Section: Emerging Issuesmentioning
confidence: 99%